(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The objective of the present work is to analyze the performance of businessmen in the commercial square of Maranhão from the perspective of the construction of the new State of Brazil. After suffering setbacks with independence, the political repositioning of the businessmen took place, where, among other things, they made an effort to publicly demonstrate their loyalty to the newly created Empire of Brazil. It seeks to understand the strategies used by these characters to maintain, in addition to economic power, their political influence in the region.